Redesain Pasar Sanggeng, Manokwari sebagai Fasilitas Umum Ramah Disabilitas - Cezia Jenifer Tambahani; Sita Yuliastuti Amijaya; Maria Kinanthi (ATRIUM: Jurnal Arsitektur, 2024)
Title: Redesign Sangeng Market, Manokwari as a Disability-Friendly Public Facility A market is one of the public facilities that function as a fulfillment of life’s needs and is used continuously by the community, so it must meet the needs of various groups, including groups with disabilities. Sanggeng market as a public facility faces accessibility issues for its users, especially those with disabilities. Disabilities refer to temporary or permanent limitations or loss of sensory and physical mobility capabilities. The pre-design research on the Redesign of Sanggeng Market aims to identify reference standards and design guidelines, particularly for physical disabilities. The research analysis is transformed into building design. The methods employed include a literature study on disability reference and general standards, precedent-building studies, and observations of similar cases. The analysis follows four principles of accessibility, which are applied to circulation, market support facilities, kiosk planning, and stalls. The research results encompass safety principles in circulation pathways, ease of use in guiding block and signage planning, usability principles in kiosk and stall design, and principles of independence in achieving access. This redesign significantly impacts the organization and revitalization of existing zones and functions. It is expected to contribute to city planning that embraces the principles of equality for the residents of Manokwari.